El Congreso de Lima de 1847 y los exiliados unitarios argentinos en la política exterior boliviana - Pol Colàs (Caravelle, 2024)
Foreign relations were fundamental to nineteenth-century Latin American state-building. They are consequently central to our understanding of these nation’s diverse evolution. In the present text, two diplomatic policies of the Bolivian government of José Ballivián (1841-1847) are analyzed in relation to the formation of an image of Bolivia as an independent regional actor. These policies were channeled through events such as the Congress of Lima of 1847 and the arrival of the Argentine “unitarios” exiles into the country.